2016
DOI: 10.14202/vetworld.2016.1282-1286
|View full text |Cite
|
Sign up to set email alerts
|

Chronic exposure to indoxacarb and pulmonary expression of toll-like receptor-9 in mice

Abstract: Aim:Chronic exposure to indoxacarb and pulmonary expression of toll-like receptor 9 (TLR-9) in mice.Materials and Methods:In this study, healthy male Swiss albino mice (n=30) aging 8-10 weeks were used to evaluate TLR-9 expression in lungs of mice following indoxacarb exposure with and without lipopolysaccharide (LPS). Indoxacarb was administered orally dissolved in groundnut oil at 4 and 2 mg/kg/day for 90 days. On day 91, five animals from each group were challenged with LPS/normal saline solution at 80 µg/a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 36 publications
2
3
0
Order By: Relevance
“…Microscopic investigation of the lung tissue from INDOX-administered animals showed a proliferation in fibrous tissue bundles around lung capillaries and interstitial tissues associated with inflammatory cells. Our histopathology data agreed with the findings of Kaur et al (2016) who reported that exposure to 2-mg INDOXinduced peribronchial infiltration of inflammatory cells and thickening of alveolar septa. Also, Liu et al (2016) showed considerable inflammatory cell infiltration damage and thickening in the alveolar walls in the lung sections from PQ-exposed rats.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Microscopic investigation of the lung tissue from INDOX-administered animals showed a proliferation in fibrous tissue bundles around lung capillaries and interstitial tissues associated with inflammatory cells. Our histopathology data agreed with the findings of Kaur et al (2016) who reported that exposure to 2-mg INDOXinduced peribronchial infiltration of inflammatory cells and thickening of alveolar septa. Also, Liu et al (2016) showed considerable inflammatory cell infiltration damage and thickening in the alveolar walls in the lung sections from PQ-exposed rats.…”
Section: Discussionsupporting
confidence: 92%
“…In the present setup, we demonstrated severe immunopositive COX-2 expression in bronchial epithelium regions of INDOX-administered rat lungs when compared with control animals. These findings correlated with those of Yeh et al (2006) who concluded that PQ-exposure upregulated COX-2 expression and hypothesized that INDOX, by disturbing the antioxidant status, increased pro-inflammatory factors, such as NO, which in turn led to lung cell inflammation ( Kaur et al 2016). Our findings supported the hypothesis that significant positive COX-2 expression in INDOX-administered rat lungs confirmed that inflammation was associated with histopathological, inflammatory, and biochemical changes.…”
Section: Discussionsupporting
confidence: 90%
“…Herbicide 2,4-D had been previously reported to cause lung injury [ 46 ]. Our previous work also showed long term dietary exposure to pesticide such as fipronil [ 17 , 47 ], ethion [ 20 ], lindane [ 19 ], imidacloprid [ 16 ] and indoxacarb [ 48 ] cause lung injury. In addition, similar to observations made with other pesticides [ 16 , 49 , 50 ], there was increase in blood TLC, neutrophils and lymphocytosis with the high and low dose without LPS to indicate systemic immune response.…”
Section: Discussionmentioning
confidence: 99%
“…Herbicide 2,4-D had been previously reported to cause lung injury [37]. Our previous work also showed long term dietary exposure to pesticide such as fipronil [7,38], ethion [10], lindane [9], imidacloprid [6] and indoxacarb [39] cause lung injury. In addition, similar to observations made with other pesticides [6,40,41], there was increase in blood TLC, neutrophils and lymphocytosis with the high dose alone Interestingly, integrin β1 promotes cell adhesion to the extracellular matrix and is associated with highly invasive and metastatic behaviour in SCLC [18].…”
Section: Discussionmentioning
confidence: 67%